English Learning Techniques for Students with Non-English Study Program - Rahayu, Arum Putri (STAI MA'ARIF MAGETAN, INDONESIA, 2022)
For students, communicating using English is a common thing. However, it is often difficult for them to develop it, especially when they come from non-English study programs. This makes them feel difficult and then lazy to learn. The problem that then arises is what learning techniques they apply to be willing and proficient in English, and how they apply these learning techniques. This study aims to: (i) examine the learning techniques used by STAI Ma'arif Magetan students in learning languages. English (ii) Exploring how these learning techniques are applied in communicating in English by STAI Ma'arif Magetan students. This research is a qualitativeresearch in the form of a case study. The results of this study indicate that (i) the students of STAI Ma'arif Magetan apply three techniques to improve their communication skills in English, namely effective production technique, comprehension reaction technique, and reinforcing comprehension technique. (ii) Every technique used by students to become proficient in communicating English, is applied in certain ways, namely translating, getting help, using gestures, using synonyms, using notes, translating, using sources, using notes, and translating using personal estimates. This research was studied using.